Conceptual foundations of labor motivation system for high-tech enterprises specialists in Iran - A. J. Bonyani; A. V. Vavilina (Управление)
In the context of the digitalization of the economy, the key driver for increasing the efficiency of the high-tech industry is the development of human resources. The purpose of the study is to determine the conceptual foundations of the personnel motivation system of high-tech enterprises in Iran. Based on the goal set, a number of tasks were solved. The components of the motivation system are described: subjects and objects of management, mechanisms and processes of management on the example of the Iranian company NOSA. The concept of “high technology” has been clarified, the criteria for a high-tech enterprise have been defined: a high share of companies’ costs for R&D (research and development work). The scientific novelty of the work lies in the construction of a conceptual scheme for motivating the personnel of high-tech enterprises. On the basis of empirical research, the needs of the employees of the Iranian company NOSA are determined. The presented tools: survey, questioning, testing, observation allow the head of the enterprise to determine the motives and needs of employees and, on their basis, develop or adjust the most effective system of personnel motivation in the enterprise. The object of the study is the personnel motivation system of the Iranian company NOSA. The subject is the organizational and economic aspects of motivating personnel in the high-tech sector in the context of the digitalization of the economy. The provisions outlined in the article make it possible to comprehensively present the conceptual foundations of personnel motivation systems, including those in high-tech industries.